De « On ne naît pas femme » à « On n’est pas femme ». De Simone de Beauvoir à Monique Wittig - Natacha Chetcuti (Genre, Sexualité et Société)
Revisiting the two famous quotes from Simone de Beauvoir’s “One is not born, but becomes a woman” and Monique Wittig’s “Lesbians are not women”, this article aims to discuss the concept of becoming woman. It analyzes how gender categorization is constructed in a heteronormative social system. Analyzing both Beauvoir’s and Wittig’s works, I recall the general assumption about sex differentiation, and question the way it is used in studies on gender, homosexuality and heterosexuality. How can subjects reach human status? By using masculinity to distance themselves from female conditioning or by denaturalising the sex/gender divide?